2022
DOI: 10.1109/tbme.2022.3175646
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Quantification of Ankle, Muscle, and Tendon Impedance in Humans

Abstract: Objective: Regulating the impedance of our joints is essential for the effective control of posture and movement. The impedance of a joint is governed mainly by the mechanical properties of the muscle-tendon units spanning it. Many studies have quantified the net impedance of joints but not the specific contributions from the muscles and tendons. The inability to quantify both muscle and tendon impedance limits the ability to determine the causes underlying altered movement control associated with aging, neuro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 12 publications
(55 citation statements)
references
References 46 publications
(88 reference statements)
3
52
0
Order By: Relevance
“…Muscle short-range stiffness describes the initial response to small, fast displacements prior to reflexive or volitional muscle activation and is critical in the control of posture and limb stability [35,36]. This finding is consistent with our previous results that demonstrated that our muscle stiffness estimates are similar to measurements of muscle short-range stiffness scaled to the triceps surae [20]. We do note, however, that if the stretch within the muscle or tendon was larger or slower, we would expect to observe more complex viscoelastic behavior.…”
Section: Characteristics Of Triceps Surae and Achilles Tendon Impedancesupporting
confidence: 91%
See 4 more Smart Citations
“…Muscle short-range stiffness describes the initial response to small, fast displacements prior to reflexive or volitional muscle activation and is critical in the control of posture and limb stability [35,36]. This finding is consistent with our previous results that demonstrated that our muscle stiffness estimates are similar to measurements of muscle short-range stiffness scaled to the triceps surae [20]. We do note, however, that if the stretch within the muscle or tendon was larger or slower, we would expect to observe more complex viscoelastic behavior.…”
Section: Characteristics Of Triceps Surae and Achilles Tendon Impedancesupporting
confidence: 91%
“…We refer to the relationship between MTJ displacement and the angular rotations of the ankle as the translation ratio. Specifically, to characterize ankle, muscle, and tendon impedance, we estimated ankle impedance and the translation ratio, and used these quantities to compute muscle and tendon impedance [20]. We previously demonstrated that the magnitude of the frequency response functions was nearly constant from 1 to 3 Hz, indicating that stiffness was the dominant contributor to impedance over this frequency range [20].…”
Section: Data Processing and Analysismentioning
confidence: 99%
See 3 more Smart Citations